Sistem Monitoring Bimbingan Mahasiswa dengan Menggunakan Metode Service Quality - Budi Dwi Prasetyo; Wina Witanti; Puspita Nurul Sabrina (Prosiding SISFOTEK, 2020)
The Informatics Engineering Study Program is one of the study programs in the Faculty of Science and Informatics (FSI), Jenderal Achmad Yani University (Unjani). The Informatics Engineering Study Program conducts final assignment guidance activities and students have the right to determine the supervisor to be able to guide students in final assignment activities. During their tutoring students have the right to get guidance based on the problem at hand. Student satisfaction in terms of guidance can be seen in terms of guidance time, the frequency of lecturers conducting guidance, lecturers provide solutions when guidance, student comfort during guidance and lecturers help solve the problem of student final assignments. Student guidance activities are not satisfied with the supervisors related to the guidance activities provided, therefore the head of the department has difficulty monitoring the guidance activities. The purpose of this research is to create a system that can monitor the guidance activities, evaluate the results of the guidance of the supervisor, assist students in providing guidance assessment satisfaction. The method used in this study is the service quality method, the service quality method is needed in order to improve the quality of guidance in the Informatics Engineering Study Program in Unjani in order to evaluate and make the guidance activities even better.